Social entrepreneurship : theory and practice - Praszkier, Ryszard, 1945-; Nowak, Andrzej (Andrzej Krzysztof). (Cambridge : Cambridge University Press, 2012)
'There are certain kinds of people who garner enormous satisfaction from successfully taking on a'mission impossible' and, by so doing, actually manage to change the world, sometimes in surprising ways. Such individuals are rare, and when we become aware of them and their astonishing achievements, we observe that they cannot easily be pigeonholed or defined by their own circumstances, that is to say, they are the products of rural as well as urban areas; of developing as well as developed countries; of large cities as well as remote areas; they may be Gurkhas from the Himalayan Mountains or Maasais from East Africa. They may be well-known figures, such as Mohammad Yunus recipient of the 2006 Nobel Peace Prize, or anonymous, unrecognized teachers from small villages. The question then becomes: If they are such a diverse group, what characteristics do they have in common, which allow us to identify them under one unifying rubric? And which of these shared attributes distinguish them from other social activists? These are the underlying questions that inform the book'--
Includes bibliographical references and index.
Keywords: Social entrepreneurship